Millennium Development Goals: how public health professionals perceive the achievement of MDGs - Marta Lomazzi (Global Health Action, 2014)
Background: There have been various consultations on the Millennium Development Goals (MDGs) by different groups. However, even if it is clear that the health sector has led the development success of the MDGs, only a few MDG reports consider public health experts’ points of view and these are mainly government driven. Designs: The World Federation of Public Health Associations (WFPHA) has executed a global survey to consult public health professionals worldwide concerning the implementation and achievements of the MDGs.The survey was conceived by WFPHA health professionals and promulgated online. Public health professionals and organisations dealing with MDGs responded to the survey. Content analysis was conducted to analyse the data. Results: Survey participants attributed the highest importance worldwide to MDGs dealing with women, poverty and hunger reduction, and disease prevention and management. Moreover, they underlined the role of education, referring both to school children and professionals. In high and upper-middle income countries, environmental challenges also received considerable attention.Notably, respondents underlined that weak governance and unstable political situations, as well as the gap between professionals and politicians, were among the main causes that detracted from MDG achievements. Conclusion: The public health workforce felt it would be imperative to be included from the outset in the design and implementation of further goals. This implies that those professionals have to take an active part in the political process leading to a new and accountable framework.